Lectotypification of Didymaea mexicana Hook. f. (Rubiaceae, Rubieae) and the identity of D. alsinoides (Schltdl. & Cham.) Standl. - Lorence, David (Instituto de Ecología, A.C., 2009)
The name Didymaea alsinoides (Schltdl. & Cham.) Standl. has been incorrectly applied to a common and wide-ranging Mexican and Central American species whose correct identity is Didymaea mexicana Hook. f. In this paper a lectotype is selected and designated for D. mexicana. The characters separating these two frequently confused species are discussed. Further systematic studies of the genus Didymaea are suggested.